2007
DOI: 10.1099/mic.0.2006/002725-0
|View full text |Cite
|
Sign up to set email alerts
|

An asparagine oxygenase (AsnO) and a 3-hydroxyasparaginyl phosphotransferase (HasP) are involved in the biosynthesis of calcium-dependent lipopeptide antibiotics

Abstract: Nonribosomal peptides contain a wide range of unusual non-proteinogenic amino acid residues. As a result, these complex natural products are amongst the most structurally diverse secondary metabolites in nature, and possess a broad spectrum of biological activities. b-Hydroxylation of amino acid precursors or peptidyl residues and their subsequent processing by downstream tailoring enzymes are some of the most common themes in the biosynthetic diversification of these therapeutically important peptides. Identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 39 publications
0
46
0
1
Order By: Relevance
“…One commonly encountered modification is the formation of β-hydroxy amino acids. The resulting hydroxylated amino acid is more hydrophilic than its precursor and often participates in secondary reactions (2), including further oxidation (3), glycosylation (4,5), methylation (6), phosphorylation (7), and macrolactonization during antibiotic heterocyclization (8). Many of the nonribosomal peptides that are modified in this fashion are mainstays of the pharmaceutical industry for use as chemotherapeutics and antimicrobial agents, such as the widely used antitumor drug bleomycin and the teicoplanin group of glycopeptide antibiotics (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One commonly encountered modification is the formation of β-hydroxy amino acids. The resulting hydroxylated amino acid is more hydrophilic than its precursor and often participates in secondary reactions (2), including further oxidation (3), glycosylation (4,5), methylation (6), phosphorylation (7), and macrolactonization during antibiotic heterocyclization (8). Many of the nonribosomal peptides that are modified in this fashion are mainstays of the pharmaceutical industry for use as chemotherapeutics and antimicrobial agents, such as the widely used antitumor drug bleomycin and the teicoplanin group of glycopeptide antibiotics (5).…”
mentioning
confidence: 99%
“…Amino acid β-hydroxylation in natural product biosynthetic pathways has been shown to be catalyzed by either nonheme iron-containing alpha-ketoglutarate (αKG)-dependent dioxygenase enzymes (7,9) or cytochrome P450 monooxygenases (10). The high C-H bond strength at the β-carbon of the amino acid (∼85 kcal∕mol) necessitates the formation of a potent oxidant, which is accommodated by the formation of activated and highly reactive metal-oxygen adducts by these enzymes, Fe IV -oxo (11) and Fe IV -oxo heme π-cation radical (reviewed in refs.…”
mentioning
confidence: 99%
“…Downsteam of asnO is another gene that encodes a protein similar to a number of ATP-dependent phosphotransferases, which was suggested to phosphorylate the CDA 3-OHAsn residue. As predicted, deletion of the AsnO encoding gene results in a mutant strain (∆asnO), which produces new CDA variants possessing exclusively Asn residues at position 9 (CDA5b, 5a, 6a) [9]. Similarly, deletion of the putative phosphotransferase encoding gene resulted in a mutant (∆hasP) which, when grown under conditions that favor phosphorylation of CDA, produces exclusively non-phosphorylated CDAs.…”
Section: Origins Of the Nonproteingenic Amino Acid Precursorsmentioning
confidence: 83%
“…Similarly, deletion of the putative phosphotransferase encoding gene resulted in a mutant (∆hasP) which, when grown under conditions that favor phosphorylation of CDA, produces exclusively non-phosphorylated CDAs. In addition, Strieker et al overproduced AsnO and have shown that the enzyme is a nonhaem Fe(II)/2-oxoglutarate-dependent oxygenase that β-hydroxylates free Asn [10], as we had earlier proposed [9]. Currently, it is suggested that hydroxylation of Asn occurs prior to activation and incorporation into the CDA lipopeptide core and that phosphorylation is most likely to occur during or after lipopeptide assembly (Fig.…”
Section: Origins Of the Nonproteingenic Amino Acid Precursorsmentioning
confidence: 86%
See 1 more Smart Citation